EXPERIENTIAL VIRTUAL URBAN ENVIRONMENTS: A PRELIMINARY INVESTIGATION - Ghani, Izham; Abdul Rahman, Norhafizah; Mat Nayan, Nadiyanti; Bahaluddin, Azrul (PLANNING MALAYSIA, 2018)
Virtual reality (VR) technologies enable users to be virtually immersed in reconstructed cities and streets from around the globe. Immersive technologies could provide users a suggestive sensation of “being there” in a reconstructed virtual urban environments (VUE). This research argues that experiential VUE could promote better understanding of a place while offering unique interactions within its surrounding elements. The aim of this research is to present a preliminary study of the factors determining place experience in a VUE. This research examines two related VUE case studies that offer real-time navigation via a 3D virtual environment (VE) platform to analyse the functionality of the offered interactions and user experience via its contents. Although preliminary investigations have shown some promising results in real-time virtual city walkthroughs, there are still some issues that still need to be addressed in order to provide experiential contents. Based on the findings, this research suggests future VUE improvements focusing on contextual setting, interactivity, navigation, level of details, viewpoints and auditory elements to provide an experiential walkthrough within a VUE. Findings from the case studies would assist and identify specific elements suitable for future development of more meaningful and experiential VUE in the Malaysian context.